Generation of New Hybridoma UTM-Ha Secreting Monoclonal Antibody Specific to Acanthamoeba species Isolated from Corneal Infection - Rasheed, Hala Abdul Kareem; Amin, Nakisah Mat; Majid, Fadzilah Adibah Abdul (International Journal of Biotechnology for Wellness Industries, 2013)
Acanthamoeba Keratitis is an important corneal infection that caused impaired vision. The Universiti Malaysia Terengganu (UMT) researcher found new species of Acanthamoeba that was being isolated from eye infection in Hospital Kuala Lumpur, which have the characteristic between Acanthamoeba polyphaga and A. castellanii named as HKL-Acantha. This study was aimed to generate specific monoclonal antibody against HKL-Acantha that eventually could be used in diagnosing eye infection among Malaysian. Two Balb/c mice were immunized with sonicated HKL-Acantha through intraperitoneal injection, and anti HKL-acantha IgG, IgM, IgA were measured using ELISA test. Sera from infected mice showed detectable anti-HKL-acantha IgM. The spleen from animal with high antibody titer around (1:81000) was used as a partner in fusion with SP2/0-Ag14 myeloma cells to produce new hybridoma cells, which were then selected and cloned using the selection medium. Two positive hybridoma clones secreting IgM antibodies were obtained and named as hybridoma UTM-Ha1 and UTM-Ha2. Both clones were secreting monoclonal IgM antibody specific to HKL-Acantha. This study suggests the potential of both hybridomas UTM-Ha1 and UTM-Ha2 to generate specific monoclonal IgM against HKL-acantha. This newly generated monoclonal IgM could be used to diagnose the presence of HKL- acantha in patients with eye infection in future.